Scenarios Workshop, Nairobi - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
In a first strategic planning workshop with non-state actors in East Africa in Nairobi on 5-6 June 2012, a vivid vision was first created for a better East Africa. Participants were asked to dream freely for a moment – the challenges to reach this vision would come later. The vision included an East African “bread basket booming†, with a woman leading a powerful East Africa Federation, ‘A Rift Silicon Valley ‘that has created 100,000 jobs, and an environment ‘so fresh it will heal your soul’ by the year 2030.